Wind Energy Explained 2009
DOI: 10.1002/9781119994367.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamics of Wind Turbines

Abstract: The study of rotor blade aerodynamic performances of wind turbine has been presented in this thesis. This study was focused on aerodynamic effects changed by blade surface distribution as well as grid solution along the airfoil. The details of numerical calculation from Fluent were described to help predict accurate blade performance for comparison and discussion with available data.The direct surface curvature distribution blade design method for two-dimensional airfoil sections for wind turbine rotors have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…But it is tedious and error-prone, and the tip loss factor makes it fairly complicated. The complex step method (Martins et al, 2000) is therefore found to be an easier way to compute the gradients, without any loss of accuracy. It also has the benefit that little additional work needs to be done when Eq.…”
Section: Gradients With Complex Stepmentioning
confidence: 99%
See 1 more Smart Citation
“…But it is tedious and error-prone, and the tip loss factor makes it fairly complicated. The complex step method (Martins et al, 2000) is therefore found to be an easier way to compute the gradients, without any loss of accuracy. It also has the benefit that little additional work needs to be done when Eq.…”
Section: Gradients With Complex Stepmentioning
confidence: 99%
“…The conceptual idea behind the complex step method is fairly simple, and for the sake of making the reader familiar with it, it is summarized here. For a proper description, the reader is referred to Martins et al (2000).…”
Section: Gradients With Complex Stepmentioning
confidence: 99%
“…In the model, this intersection was adjusted to apply the desired pressure drop value.The thrust and power coefficients were calculated by following Eq. 2 and Eq.3, Martin (2010).…”
Section: Validation Of Rotor Modelmentioning
confidence: 99%
“…Wind turbine design optimization has been an integral part of wind turbine design since the start of the wind turbine industry. The target for such optimization has varied greatly from pure aerodynamic optimization with the target to maximize the power extraction (see Manwell et al, 2010, Sørensen, 2016and Jamieson, 2018 to a more holistic turbine design where the target is to minimize the cost of the turbine through modeling the physics of the turbine components as well as their associated cost; see, e.g., Fuglsang et al (2002), Hjort et al (2009), Bottasso et al (2012), Meadows (2012), andPerez-Moreno et al (2016). Common to these approaches the connection of a set of simulation tools (e.g., BEM solver, structural solver, controller) through a cost function, leading to a fairly complicated optimization problem with a lot of design variables.…”
Section: Introductionmentioning
confidence: 99%